Imaging-guided percutaneous vertebral and paravertebral lesion biopsy: A single center experience - Onur Taydaş (Journal of Surgery and Medicine, 2020)
Aim: Percutaneous needle biopsy has been used successfully in the diagnosis of vertebral, paravertebral and disc diseases in recent years as it is a minimally invasive, safe, and effective method. The aim of this study was to share our experience with imaging-guided percutaneous vertebral and paravertebral biopsies.Methods: Images and data of 10 patients who underwent percutaneous vertebral and paravertebral biopsies between January 2018 and December 2019 were screened retrospectively through the hospital registry. The anatomical location of the lesion, guideline imaging method, number of samples taken, whether there were any complications after the procedure, needle diameter used, hemoglobin (Hb) values before and after the procedure were recorded.Results: Among 10 patients included in the study, 3 (30%) were male and 7 (70%) were female. The mean age of the patients was 63.5 (8.6) years. Biopsies were performed under computerized tomography and ultrasound guidance in nine patients and one patient, respectively. The lesion was located at the thoracic level in 4 patients (40%) and at the lumbar level in 6 patients (60%). Two samples were obtained from all patients. There were no complications. The mean Hemoglobin (Hb) values before and after the procedure were 10 (1.1) mg/dL and 10.2 (1.4) mg/dL, respectively, which were similar (P=0.91). 18G needle was used in all patients.Conclusion: Imaging-guided percutaneous vertebral and paravertebral biopsy is a safe and effective method which allows sampling for cytological, histological, and microbiological analysis. In the future, imaging techniques and biopsies will be increasingly used in the diagnosis of vertebral and paravertebral lesions.